End-tidal carbon dioxide tension is a reliable surrogate of arterial carbon dioxide tension across different oxygen, carbon dioxide and barometric pressures. Issue 2 (17th April 2023) - Manferdelli, Giorgio; Narang, Benjamin J.; Bourdillon, Nicolas; Debevec, Tadej; Millet, Grégoire P.
Accurate measurement of arterial carbon dioxide partial pressure ( P aCO2 ) is critical in emergency medicine as a marker of sufficient alveolar ventilation [1], and in human physiology to understand respiratory and cerebrovascular regulation [2]. The current gold-standard technique to measure P aCO2 is through arterial catheterisation and analysis of blood gases, although arterialised capillary blood ( e.g. earlobe or fingertip) is often used to alleviate the invasiveness and risk associated with arterial sampling [3]. End-tidal CO2 tension provides an accurate estimation of P aCO2 in healthy awake individuals over an extensive range of CO2 pressures induced by 17 environmental conditions combining different O2, CO2 and barometric pressures https://bit.ly/3YuKPAY